Efectos del silicio en la resistencia a plagas en el cultivo de arroz (Oryza sativa L.) - Tapia Cortez, Jimmy Alexander (2019)
The work consisted of gathering information from different sources of information on rice cultivation (Oryza sativa L), this crop is of great importance because it contributes to the feeding of the world and national population, many of the Ecuadorian families that are dedicated to the cultivation of Rice consists of this single source of income, so finding information that improves its production is an option that would change the economic conditions of a large number of individuals in the country. Ecuador sows approximately 343,936 hectares, of which 332,988 are harvested, achieving a production of 1,239,269 t. In the province of Los Ríos approximately 114 545 hectares are sown, of which 110 386 hectares are harvested, reaching a production of 359 569 t. The average yield of husk rice with 20% humidity and 5% impurities was 3.92 t / ha (INEC 2017). The application of silicon in rice cultivation efficiently improves the response to attack by pests and diseases, by allowing the rice plant to develop strong leaves, stems and roots. The formation of a thick layer of epidermal cells reduces the susceptibility of the plant to fungal and bacterial diseases and to attack by insects. Rice plants properly stocked with Silicon have erect leaves and growth habits. This contributes to the efficient use of light and therefore to the efficient use of N (AGRI-CROP. 2019). The use of silicon in rice cultivation is an effective measure for all farmers to improve their yield, offering the end consumer a much more nutritious and healthy product